2014
DOI: 10.1089/scd.2014.0110
|View full text |Cite
|
Sign up to set email alerts
|

Human Transgene-Free Amniotic-Fluid-Derived Induced Pluripotent Stem Cells for Autologous Cell Therapy

Abstract: The establishment of a reliable prenatal source of autologous, transgene-free progenitor cells has enormous potential in the development of regenerative-medicine-based therapies for infants born with devastating birth defects. Here, we show that a largely CD117-negative population of human amniotic fluid mesenchymal stromal cells (AF-MSCs) obtained from fetuses with or without prenatally diagnosed anomalies are readily abundant and have limited baseline differentiation potential when compared with bone-marrow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 36 publications
0
38
0
Order By: Relevance
“…More recently, transgene-free iPSC were derived from AFSC employing a Sendai virus-based vector and were demonstrated to efficiently differentiate into neural progenitors capable of engrafting into the brain parenchyma of rats. 48 However, the iPSC were derived and cultured in undefined ESC-conditioned medium on MEF layers though they could be transferred onto feeder-free surfaces. Our work complements this study in that it provides a method for derivation and culture of iPSC from AFSC in a chemically defined medium.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, transgene-free iPSC were derived from AFSC employing a Sendai virus-based vector and were demonstrated to efficiently differentiate into neural progenitors capable of engrafting into the brain parenchyma of rats. 48 However, the iPSC were derived and cultured in undefined ESC-conditioned medium on MEF layers though they could be transferred onto feeder-free surfaces. Our work complements this study in that it provides a method for derivation and culture of iPSC from AFSC in a chemically defined medium.…”
Section: Discussionmentioning
confidence: 99%
“…The reactivation of the dormant X chromosome may be associated with genomic reprogramming events, further supporting the significant role of AFSCs in embryogenesis [5]. CD117-negative populations of human amniotic fluid mesenchymal stromal cells (AFMSCs) are not only readily abundant for therapeutic use, but can also easily differentiate into induced pluripotent stem cells (iPSCs) with the use of nonintegrating Sendai viral vectors encoding for OCT4, SOX2, KLF4 and cMYC [6]. Moreover, Jiange et al [6] have revealed the potential of iPSCs to imitate human embryonic stem cells, noting their ability to form relatively homogenous populations of neural progenitors, and to show engraftment potential in vivo.…”
Section: Stemness Of Cells Derived From the Amniotic Fluidmentioning
confidence: 97%
“…CD117-negative populations of human amniotic fluid mesenchymal stromal cells (AFMSCs) are not only readily abundant for therapeutic use, but can also easily differentiate into induced pluripotent stem cells (iPSCs) with the use of nonintegrating Sendai viral vectors encoding for OCT4, SOX2, KLF4 and cMYC [6]. Moreover, Jiange et al [6] have revealed the potential of iPSCs to imitate human embryonic stem cells, noting their ability to form relatively homogenous populations of neural progenitors, and to show engraftment potential in vivo. In vitro, these neural progenitor cells display the ability to differentiate into astrocytes and mature neurons [6].…”
Section: Stemness Of Cells Derived From the Amniotic Fluidmentioning
confidence: 99%
See 1 more Smart Citation
“…Amniotic cells have been reprogrammed with viral vectors, including both integrating (Anchan et al 2011;Fan et al 2012;Galende et al 2010;Ge et al 2012;Li et al 2009;Li et al 2012;Lu et al 2011;Wolfrum et al 2010;Ye et al 2010) and nonintegrating systems (Jiang et al 2014), that efficiently deliver reprogramming transgenes. Leaky or reactivated expression of cell populations that we established in a previous work (Wilson et al 2012).…”
Section: Introductionmentioning
confidence: 99%